Clinical and Functional Characterization of Gain‐of‐Function ABL1 Variants Expands the Phenotypic Spectrum of CHDSKM - Yuri A. Zarate; Seungjae Oh; Julie E. Saldana Guzman; J. Paige Matheny; Siobhan Belgarde; Jenny P. Garzon; Carlos E. Prada; Zoey Trueblood; Moin U. Vera; Konstantin V. Korotkov; Emilia Galperin (American Journal of Medical Genetics Part A, 2026)
ABSTRACT Germline gain‐of‐function (GOF) variants in ABL1 cause congenital heart defects and skeletal malformations syndrome (CHDSKM), a multisystem developmental disorder characterized by congenital heart disease, skeletal abnormalities, dysmorphic features, and variable developmental delay. More recently, biallelic loss‐of‐function variants and ABL haploinsufficiency have been associated with distinct phenotypes, expanding the allelic spectrum of ABL1 ‐related disorders. We report three individuals with ABL1 variants. A female infant with tetralogy of Fallot, critical pulmonary stenosis, covered omphalocele, and a lethal outcome was found by rapid trio genome sequencing to harbor a de novo likely pathogenic ABL1 variant, NM_007313.2:c.354G>T p.(Trp118Cys). We also provide updated clinical follow‐up of a previously reported individual and describe a third individual, both carrying the recurrent p.(Tyr245Cys) variant. Functional studies were performed and support a GOF mechanism. Similar activation was observed for Tyr245Cys despite the differences in clinical severity. Our findings expand the phenotypic spectrum of ABL1‐related CHDSKM to include severe conotruncal heart disease and covered omphalocele. The comparison of two biochemically activating ABL1 variants demonstrates substantial clinical variability despite a shared molecular mechanism. Furthermore, the overlap between ventral body wall abnormalities in GOF disease and omphalocele associated with ABL1 haploinsufficiency suggests that precise regulation of ABL1 signaling is critical for normal ventral body wall formation.